Reconstructing Women's Status in Mowea Sarapu: Customary Divorce, Maqasid al-Shari'ah, and Gender Justice in Tolaki Muslim Legal Pluralism, Indonesia - Muh. Akbar Fhad Syahril; Zainuddin Zainuddin; Anatolijs Krivins; Wiwin Wiwin; Nurhaedah Hasan; Hardi Lestari Adi Hafid (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This study examines the practice of Mowea Sarapu within the Tolaki Muslim community in Indonesia, focusing on the husband as the primary unit of analysis. In this context, the husband symbolically